2019
DOI: 10.11648/j.ajhr.20190706.12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Group b Streptococcus, Its Associated Factors and Antimicrobial Susceptibility Pattern Among Pregnant Women Attending Antenatal Care at Arbaminch Hospital, South Ethiopia

Abstract: Background: Group B Streptococcus colonization of the gastrointestinal and genital tracts of pregnant women usually remains asymptomatic; even if it is the critical determinant of infection in neonates and young infants. It causes early and late onset of invasive Group B Streptococcus (GBS) disease manifesting as septicemia, meningitis and pneumonia. Now it is recognized as an important cause of maternal and neonatal morbidity and mortality in many parts of the world including Ethiopia where the magnitude of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
3
13
2
Order By: Relevance
“… 40 However, it was lower in comparison to reports from South Africa (48.2%), 16 Gambia (33.7%), 41 the United Kingdom (29.4%) 42 and USA (35%). 12 But the present finding is higher compared to the 7.2 −13.7% prior reports from other parts of Ethiopia, 18 , 25 , 43 , 44 and 6.1% in China. 20 The difference in the percentage of GBS colonization could be due to variation in the type of swabs used, sample collection strategy and composition, microbiological protocols used to isolate and identify GBS.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“… 40 However, it was lower in comparison to reports from South Africa (48.2%), 16 Gambia (33.7%), 41 the United Kingdom (29.4%) 42 and USA (35%). 12 But the present finding is higher compared to the 7.2 −13.7% prior reports from other parts of Ethiopia, 18 , 25 , 43 , 44 and 6.1% in China. 20 The difference in the percentage of GBS colonization could be due to variation in the type of swabs used, sample collection strategy and composition, microbiological protocols used to isolate and identify GBS.…”
Section: Discussioncontrasting
confidence: 87%
“…The 35.2% MDR GBS isolates found from the mothers in the present study is in line with a report from Addis Ababa, Ethiopia (43.9%). 54 However, it was higher compared to reports from Mekelle (10.5%) 43 and Arbaminch (8.3%), 44 Ethiopia. Likewise, 36.4% of GBS isolated from newborns were MDR in the present study.…”
Section: Discussioncontrasting
confidence: 58%
“…However, erythromycin which is recommended in case of allergy to beta-Lactamines was not active on some strains. Similar results were reported by Shiferawu et al 41 in South Ethiopia with 100% susceptibility of strains to penicillin G.…”
Section: For Example Increasing Epidemiological Studies Have Demonstrated the Relationship Between Obesity And Gbs Colonisation In Pregnasupporting
confidence: 90%
“…for other samples, P = .070). 41 Second, the study design is crosssectional, in which both cause and effect are measured at the same time; therefore, we can only describe associations between associated factors and GBS colonisation, not a causal conclusion. The pathophysiological mechanisms responsible for the observed associations are unknown.…”
Section: For Example Increasing Epidemiological Studies Have Demonstrated the Relationship Between Obesity And Gbs Colonisation In Pregnamentioning
confidence: 99%
“…First, only the vagina was used as a sampling site, with a consequence of underestimation of the true prevalence of GBS. However, the latest system review on pregnant women revealed that there was no significant difference in GBS colonisation according to sample sites (11% for both vaginal and rectal samples, 11% for vaginal samples, and 8% for other samples, P = 0.070) 44 . Second, the study design is a cross-sectional, in which both cause and effect are measured at the same time; therefore, we can only describe associations between influencing factors and GBS colonisation, not a causal conclusion.…”
Section: Discussionmentioning
confidence: 94%